ANIMAL MODELS OF DIABETIC NEPHROPATHY - Azizah, Dira Ummul; Bahtiar, Anton; ANGELINA, MARISSA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Diabetic nephropathy (DN) is the most common complication of diabetes mellitus (DM). It is characterized by high blood glucose levels or hyperglycemia and is accompanied by changes in lipid, carbohydrate, and protein metabolism which can lead to an increased risk of complications due to vascular disease. DN is probably the most insidious among these complications, causing substantial morbidity and mortality. In this article, we will review the literature on animal models of diabetes. We will discuss several species as animal models for Type 1 and 2 diabetes, including zebrafish, rabbits, mice, rats, and rat models. This article also provides various methods used in research with model animals and presents the required result for studying diabetic DN.